Factors influencing long-term quality of life and depression in German liver transplant recipients: a single-centre cross-sectional study - Zahn, Alexandra; Seubert, Lisa; Jünger, Jana; Schellberg, Dieter; Weiss, Karl Heinz; Schemmer, Peter; Stremmel, Wolfgang; Sauer, Peter; Gotthardt, Daniel (Annals of transplantation, 2013)
Background - Health-related quality of life (HRQOL) following orthotopic liver transplantation (OLT) has become increasingly important. Therefore, we aimed to identify factors affecting HRQOL after OLT. - Material and Methods - This cross-sectional, single-centre study surveyed 281 OLT patients. Survey tools included the Short Form (SF-36) Health Survey, the Patient Health Questionnaire 9 (PHQ9), and a self-designed employment questionnaire. Patient medical records were reviewed. - Results - Participants included 187 men (mean age at OLT: 50 [±11; 13-69] years). Primary indications for OLT were viral hepatitis (28%), alcoholic liver disease (35%), cholestatic liver disease (11%), and others (26%). Follow-up ranged from 2 to 136 months. Clinical factors associated with improved HRQOL were age ≤45 years at OLT and current MELD score <=≤13. Time after OLT and indication for transplantation affected SF-36 HRQOL. SF-36 physical component summary scales plateaued at 3-years post-OLT and then stabilized. For the SF-36 HRQOL, scores were the lowest in all domains for OLT recipients transplanted for chronic viral hepatitis and for unemployed patients, whereas sex and number of transplantations showed no significant differences. The PHQ9 results showed that depression was significantly more frequent among patients with current MELD score ≥ 13 or impaired liver function and those transplanted for chronic viral hepatitis or unemployed patients. Age and sex did not influence PHQ9 results. - Conclusions - Medical and psychosocial support is crucial for long-term HRQOL after OLT. Developing multidisciplinary interventions to address issues such as employment, age, MELD score, and liver function may improve long-term HRQOL in these patients.
Gesehen am 26.07.2021